Karakterisasi Buah dan Penentuan Saat Masak Fisiologi Benih Beberapa Genotipe Cabai (Capsicum annuum L.) - Suharsi, Tatiek Kartika; Syukur, Muhamad; Wijaya, Arief Riza (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACTIdentification of fruit and seed characters when they reach physiological maturity is very important to get high qualiy chili seed. The purpose of the research was to study the fruit characters and to determine seed physiologycal maturity of six chili genotipes (Capsicum annuum L.) i.e. Anies 1, Anies 2, Seloka 1, Seloka 2, Seloka 3 and SSP. Characterization was assayed at 32, 35, 38, 41, 44 DAA. Chili seed was taken from two groups of branches, lower branches (2nd-5th branches) and upper branches (6-7th branches). The result revealed that seed physiological maturity was achieved at 38-44 DAA, that was indicated by changes of the fruit color from brown to red (Anies 1) and dark green to red on five others genotipe; maximum seed dry weight, seed viability and vigor. When the seed reached physiological maturity, SSP’s had the longest fruit but fruit diameter and weight, seed number and seed weight per fruit was the lowest. However, SSP seed rendement was the highest. Flowers of lower branches developed faster, their fruits size, seed dry weight, and seed number was significantly higher than the upper branches. Nevertheles the seed viability and vigor was not different between lower and upper branches.Keywords: fruit color, seed dry weight, seed viability, seed vigor